2017
DOI: 10.1007/s13142-017-0479-z
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Eating for Life English as a second language curriculum: applying the RE-AIM framework to evaluate a nutrition education intervention targeting cancer risk reduction

Abstract: Medically underserved US immigrants are at an increased risk for death from preventable or curable cancers due to economic, cultural, and/or linguistic barriers to medical care. The purpose of this study was to describe the evaluation of the pilot study of the Healthy Eating for Life (HE4L) English as a second language curriculum. The Reach, Effectiveness Adoption, Implementation, Maintenance (RE-AIM) model was used to design a mixed-methods approach to the evaluation of the HE4L curriculum. Successful impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Implementation in this paper is defined as the initiation of a health intervention rather than a widespread upscaling and thus this section focused on intervention fidelity. The RE-AIM (reach, efficacy, adoption, implementation and maintenance) framework was chosen as it has been validated as a tool to plan, evaluate and to assess the impact of a variety of health care and health prevention programs [ 35 37 ]. Briefly, ‘reach’ refers to participation and representativeness of the target population.…”
Section: Methodsmentioning
confidence: 99%
“…Implementation in this paper is defined as the initiation of a health intervention rather than a widespread upscaling and thus this section focused on intervention fidelity. The RE-AIM (reach, efficacy, adoption, implementation and maintenance) framework was chosen as it has been validated as a tool to plan, evaluate and to assess the impact of a variety of health care and health prevention programs [ 35 37 ]. Briefly, ‘reach’ refers to participation and representativeness of the target population.…”
Section: Methodsmentioning
confidence: 99%
“…Another innovation in the assessment of implementation outcomes is the RE-AIM Qualitative Evaluation for Systematic Translation (RE-AIM QuEST), a mixed methods framework developed by Forman and colleagues (31). The RE-AIM (Reach, Efficacy/Effectiveness, Adoption, Implementation, and Maintenance) framework is often used to monitor the success of intervention effectiveness, dissemination, and implementation in real-life settings (35), and has been used to guide several mixed method implementation studies (6, 50, 54, 79, 82, 85). The RE-AIM QuEST framework represents an attempt to provide guidelines for the systematic application of quantitative and qualitative data for summative evaluations of each of the five dimensions.…”
Section: Procedures For Measuring Evaluation Outcomesmentioning
confidence: 99%
“…In addition to ways to improve intervention reach , the use of RE-AIM at this scoping phase was helpful in determining factors that could support the implementation and maintenance of a new cancer prevention curriculum. A major implementation challenge reported in the literature has been to cover curriculum content goals while simultaneously building English literacy skills according to course requirements and student level ( Morony et al, 20182018 , Martinez et al, 2017 ). In the current study, results suggested that a health curriculum, with core skills requirements embedded, may be more likely to be adopted by teachers who are looking for materials to meet students’ skills requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing the ‘real-world’ translation potential of any applied intervention is critical if uptake is the goal. Martinez and colleagues ( Martinez et al, 2017 ) analysed their ESL intervention trial (see ( Duncan et al, 2013 ) and then, using the RE-AIM translational research evaluation framework, retrospectively investigated the curriculum’s translation potential. RE-AIM was developed by Glasgow et al (1999) with the goal of helping researchers establish external validity (i.e., the generalizability of research findings to different populations and settings) in addition to the more common focus on internal validity (i.e., efficacy) when evaluating the impact of community-based and clinical interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation